Simulation of Soil Organic Carbon Effects on Long-Term Winter Wheat (Triticum aestivum) Production Under Varying Fertilizer Inputs - Ghaley, Bhim B.; Wösten, Henk; Olesen, Jørgen E.; Schelde, Kirsten; Baby, Sanmohan; Karki, Yubaraj K.; Børgesen, Christen D.; Smith, Pete; Yeluripati, Jagadeesh; Ferrise, Roberto; Bindi, Marco; Kuikman, Peter; et al. (Frontiers in Plant Science, 2018)
SOC (soil organic carbon) has a vital role to enhance agricultural productivity and for mitigation of climate change. To quantify SOC effects on productivity, process models serve as a robust tool to keep track of multiple plant and soil factors and their interactions affecting SOC dynamics. We used soil-plant-atmospheric model viz. DAISY, to assess effects of SOC on nitrogen (N) supply and plant available water (PAW) under varying N fertilizer rates in winter wheat(Triticum aestivum) in Denmark. The study objective was assessment of SOC effects on winter wheat grain and aboveground biomass accumulation at three SOC levels (low:0.7% SOC ; reference: 1.3% SOC and high: 2% SOC) with five nitrogen rates (0-200 kg N ha-1) and PAW at low, reference and high SOC levels. The three SOC levels had significant effects on grain yields and aboveground biomass accumulation at only 0-100 kg N ha-1 and the SOC effects decreased with increasing N rates until no effects at 150-200 kg N ha-1. PAW had significant positive correlation with SOC content, with high SOC retaining higher PAW compared to low and reference SOC. The mean PAW and SOC correlation was given by PAW% = 1.0073 ×SOC% + 15.641. For the 0.7-2% SOC range, the PAW increase was small with no significant effects on grain yields and aboveground biomass accumulation. The higher winter wheat grain and aboveground biomass was attributed to higher N supply in N deficient wheat production system. Our study suggested that building SOC enhances agronomic productivity at only 0-100 kg N ha-1. Maintenance of SOC stock will require regular replenishment of SOC, to compensate for the mineralization process degrading SOC overtime. Hence, management can maximize realisation of SOC benefits by building up SOC and maintaining N rates in the range 0-100 kg N ha-1, to reduce the off-farm N losses depending on the environmental zones, land use and the production system.